PEMANFAATAN IJUK DAN LIMBAH PARTIKEL KAYU ALAU SEBAGAI BAHAN BAKU PAPAN PARTIKEL (Utilization of Palm Fibers and Wood Particle Waste of Alau as Particle Board Materials): Grace Sisca, Sarinah, Gimson Luhan - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTParticle board is the multiuse materials that could be used as substitute materials of the solid wood as to review light in weight construction, furniture raw material, etc. Wood particle waste of alau is produced by saw mill or wood furniture as the waste, whereas the palm fibers is produced from non forestry plants of palm that grow well at the peat-swamp lands. This research was aimed to analyze the mixed of palm fibers and wood particle waste of alau to produce the particle board materials. Some combination of treatments were tested to produce the valuable particle board. The research results showed that the exact combination between palm fibers and wood particle waste of alau produced the valuable particle board materials with up to standars of JIS A 5908:2003 for review physical properties. The highest density of particle board and its stability dimension were attained at the moment of the composition between palm fibers and wood particle waste of alau namely 25:75 with glue content namely 40% . Keywords: palm fibers, particle board, physical properties,waste of alau